Design, Construction and Control of a Scara Manipulator with 6 Degrees of Freedom - Urrea-Onate, E; Pascal-Mamani, J (Universidad Nacional Autonoma de Mexico, Centro de Ciencias Aplicadas y Desarrollo Tecnologico, 2016)
The design and implementation of a robot manipulator with 6 degrees of freedom (DOF), which constitutes a physical platform on which a variety of control techniques can be tested and studied, are presented. The robot has mechanical, electronic and control systems, and the intuitive graphic interface designed and implemented for it allows the user to easily command this robot and to generate trajectories for it. Materializing this work required the integration of knowledge in electronics, microcontroller programming, MatLab/Simulink programming, control systems, communication between PCs and microcontrollers, mechanics, assembly, etc. © 2016 Universidad Nacional Autónoma de México, Centro de Ciencias Aplicadas y Desarrollo Tecnológico